2019
DOI: 10.1080/21645515.2019.1589288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a risk score to predict future Clostridium difficile disease using UK primary care and hospital data in Clinical Practice Research Datalink

Abstract: We evaluated the applicability of a Clostridium difficile infection (CDI) risk index developed for patients at hospital discharge to identify persons at high-risk of CDI in a primary care population. This retrospective observational study used data from the UK Clinical Practice Research Datalink, linked with Hospital Episodes Statistics. The risk index was based on the following patient characteristics: age, previous hospitalizations, days in hospital, and prior antibiotics use. Individual risk scores were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…1,45 The strongest risk factor for developing CDI is recent antibiotic use (within 3 months), and increased duration of exposure and number of antibiotics used are associated with higher risk for developing CDI. 9,43,[46][47][48] Although most antibiotics can change the colonic bacterial milieu leading to dysbiosis, drugs such as clindamycin, ampicillin, penicillin with beta-lactamase inhibitors, fluoroquinolones, and thirdgeneration cephalosporins are more commonly associated with developing CDI. 46,49 Other risk factors for CDI include having contact with a health care facility whether as an inpatient or an outpatient.…”
Section: Methodsmentioning
confidence: 99%
“…1,45 The strongest risk factor for developing CDI is recent antibiotic use (within 3 months), and increased duration of exposure and number of antibiotics used are associated with higher risk for developing CDI. 9,43,[46][47][48] Although most antibiotics can change the colonic bacterial milieu leading to dysbiosis, drugs such as clindamycin, ampicillin, penicillin with beta-lactamase inhibitors, fluoroquinolones, and thirdgeneration cephalosporins are more commonly associated with developing CDI. 46,49 Other risk factors for CDI include having contact with a health care facility whether as an inpatient or an outpatient.…”
Section: Methodsmentioning
confidence: 99%
“…They show that age older than 65 years and Hyspanic race are risk factors for CDI in febrile neutropenia 39 . Moreover, in a study by Marley et al it is shown that having been hospitalized within 90 days from the CDI onset, having used 4 or more classes of antibiotics in the same time frame and an age over 75 years are the independent risk factors with the highest association to the onset of CDI 41 …”
Section: Considerations About the Risk Of Infection With Anti‐il‐23p1mentioning
confidence: 99%
“…39 Moreover, in a study by Marley et al it is shown that having been hospitalized within 90 days from the CDI onset, having used 4 or more classes of antibiotics in the same time frame and an age over 75 years are the independent risk factors with the highest association to the onset of CDI. 41 With regards to the use of drugs which modulates the immune system, and in particular the IL-23/IL-17 axis, conflicting evidences exist. IL-17 has a role in immune defense against extracellular bacterial and fungal infections.…”
Section: Considerations About the Risk Of Infection With Anti-il-23p1...mentioning
confidence: 99%
“…The highest AUROC achieved was a modest 0.75. Marley et al [28] validated the Baggs score in a UK-based cohort of over 2 million individuals drawn from a general, mostly outpatient population with a 1-year cumulative CDI incidence of only 0.02%. The overall AUROC was 0.89, and using a cutoff of at least 7 yielded a sensitivity of 80% and specificity 87%.…”
Section: Simple Incident Clostridioides Difficile Infection Risk Pred...mentioning
confidence: 99%